Cis-4-[18F]fluoro-L-proline PET/CT molecular imaging quantifying liver collagenogenesis: No existing fibrotic deposition in experimental advanced-stage alcoholic liver fibrosis - Duan, Na; Chen, Hongxia; Pi, Liya; Ali, Youssef; Cao, Qi (Frontiers in Nuclear Medicine, 2022)
Heavy alcohol drinking-induced alcoholic steatohepatitis may progress to advanced-stage alcoholic liver fibrosis (AALF)/cirrhosis. The lack of non-invasive imaging technique for diagnosis of collagenogenesis can lead to incurable liver fibrosis. We aims to use cis-4-[18F]fluoro-L-proline ([18F]Proline) micro PET as a non-invasive imaging to quantify liver collagenogenesis in HSC of experimental AALF. [18F]Proline micro PET/CT imaging showed higher SUVmax in liver(4.90 ± 0.91 vs. 1.63 ± 0.38, p < 0.01), higher normalized liver/brain ratio(12.54 ± 0.72 vs. 2.33 ± 0.41, p < 0.01), and higher normalized liver/thigh ratio (6.03 ± 0.78 vs. 1.09 ± 0.09, p < 0.01) in AALF mice than controls, which are all positive correlated with fluoro-proline-induced levels of collagen in liver tissue(r value ≥ 0.93, p < 0.01) in AALF mice, but not correlated with existing liver collagen.